1993
DOI: 10.1111/j.1460-2695.1993.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Stress Intensity Factors for Cracks in Turbine Discs

Abstract: Stage-I1 fatigue crack growth paths in firtree fixtures have been predicted using a photoelastic technique. Initiation was assumed to occur at the edge of contact on the load-bearing flanks and, subsequently, the cracks were extended in the direction of the maximum circumferential stress. After a short initial length, in which propagation was perpendicular to the contact surface, the direction of crack growth was, in a broad sense, equivalent to the hoop direction in the disc. Stress intensity factors were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Fracture mechanics studies using transmission photoelasticity require fine slits to be introduced into epoxy models of engineering components [16,17]. Several methods have been developed to determine K I and K II using the full field of data surrounding the slit tip [18,19].…”
Section: Overview Of Full Field Techniques For Crack Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture mechanics studies using transmission photoelasticity require fine slits to be introduced into epoxy models of engineering components [16,17]. Several methods have been developed to determine K I and K II using the full field of data surrounding the slit tip [18,19].…”
Section: Overview Of Full Field Techniques For Crack Analysismentioning
confidence: 99%
“…Several methods have been developed to determine K I and K II using the full field of data surrounding the slit tip [18,19]. Nurse and Patterson [16] also developed a photoelastic method to predict the direction of crack growth using the theory that long cracks usually grow under mode I loading in direction perpendicular to maximum tangential stress. They found that when K II /K I is less than 0.7, this direction is approximately equivalent to the axis of symmetry observed in the isochromatic fringes loops and so one can predict the direction of crack growth.…”
Section: Overview Of Full Field Techniques For Crack Analysismentioning
confidence: 99%
“…The CJP model is based on Nurse and Patterson’s approach [ 26 ] for the description of Muskhelishvili’s complex potentials [ 9 ] as Fourier series. The stress tensor components surrounding a fatigue crack according to this model are given by Equations (1)–(3) [ 1 ]: σ x = r −1/2 {−1/2 (A + 4B + 8E) cos(θ/2) − 1/2 B cos(5θ/2) − 1/2 E [ln(r) (cos(5θ/2) + 3 cos(θ/2)) + θ (sin(5θ/2)+ 3 sin(θ/2))]} + C, σ y = r −1/2 {1/2 (A − 4B − 8E) cos(θ/2) + 1/2 B cos(5θ/2) + 1/2 E [ln(r) (cos(5θ/2) − 5 cos(θ/2)) + θ (sin(5θ/2) − 5 sin(θ/2))]} − F, τ xy = r −1/2 {A sin(θ/2) + B sin(5θ/2) − E sin(θ) (ln(r) cos(3θ/2) + θ sin(3θ/2))}, where r and θ are the polar coordinates in the crack plane (see Figure 1 ), and A, B, C, E, and F are the coefficients describing the stress fields.…”
Section: Mathematical Description Of the Crack Tip Fields According T...mentioning
confidence: 99%
“…The CJP model is based on Nurse and Patterson's approach [26] for the description of Muskhelishvili's complex potentials [9] as Fourier series. The stress tensor components surrounding a fatigue crack according to this model are given by Equations ( 1)-( 3) [1]:…”
Section: Mathematical Description Of the Crack Tip Fields According T...mentioning
confidence: 99%
“…The cracks were produced artificially by introducing a short 'starter' crack at the hole and then incrementally extending the crack in a direction predicted for slow crack growth (9,10). At each increment the stress intensity factors were determined using a procedure developed by the authors (ell).…”
Section: Introductionmentioning
confidence: 99%